2022
DOI: 10.1186/s12870-022-03643-4
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of complete chloroplast genome and phylogenetic aspects of ten Ficus species

Abstract: Background The large genus Ficus comprises approximately 800 species, most of which possess high ornamental and ecological values. However, its evolutionary history remains largely unknown. Plastome (chloroplast genome) analysis had become an essential tool for species identification and for unveiling evolutionary relationships between species, genus and other rank groups. In this work we present the plastomes of ten Ficus species. Results The comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 87 publications
(87 reference statements)
3
18
1
Order By: Relevance
“…The six cp genomes of the genus Michelia ranged in size from 159,703 to 160,026 bp, with an average GC content of 39.26% and codon usage mostly ending in A/U, similar to the other cp genomes of Magnoliaceae, indicating that higher plants have a stable genome structure [5,[24][25][26]. In this study, the transfer of the gene rpl2 to the LSC region resulted in a shorter IR region and a longer LSC region in M. doltsopa, and this gene transfer is also present in a variety of angiosperms [25,[27][28][29]. This suggested that the conservation of cp genome sequences in higher plants coexists with IR boundary diversity, which in turn ensures genome diversity [14,[30][31][32].…”
Section: Characteristics Of the Cp Genomesupporting
confidence: 65%
“…The six cp genomes of the genus Michelia ranged in size from 159,703 to 160,026 bp, with an average GC content of 39.26% and codon usage mostly ending in A/U, similar to the other cp genomes of Magnoliaceae, indicating that higher plants have a stable genome structure [5,[24][25][26]. In this study, the transfer of the gene rpl2 to the LSC region resulted in a shorter IR region and a longer LSC region in M. doltsopa, and this gene transfer is also present in a variety of angiosperms [25,[27][28][29]. This suggested that the conservation of cp genome sequences in higher plants coexists with IR boundary diversity, which in turn ensures genome diversity [14,[30][31][32].…”
Section: Characteristics Of the Cp Genomesupporting
confidence: 65%
“…In this study, we implemented a comprehensive comparative analysis of 22 plastomes from Ferula , Talassia , and Soranthus . All plastomes possessed a typical circular tetrad structure with two inverted repeat regions, one SSC region, and one LSC region, which is common in other plants [ 44 46 ]. Additionally, the gene numbers, type and distribution of large repeats, number and type of SSRs, and codon usage were rather similar among these plastomes.…”
Section: Discussionmentioning
confidence: 99%
“…To date, vast comparative chloroplast genomic studies have been conducted in a wide range of taxonomic levels, such as order (such as Dipsacales [56] and Saxifragales [57]), family (such as Orchidaceae [58] and Zingiberaceae [59]), and genus (such as Camellia [60], Lindera [61], Gossypium [62], and Ficus [17,51,63]). However, less research has focused on the comparative genomics of taxa undergoing recent speciation, such as the species complex [29].…”
Section: Discussionmentioning
confidence: 99%
“…The 13 F. sarmentosa complex chloroplast genomes were combined with 36 Ficus chloroplast genomes from GenBank and 59 Ficus genomes published by Bruun-Lund et al [26]. Additionally, 18 genomes from the China National GeneBank (accession number: CNP0001337) and Genome Sequence Archive (accession number: PRJCA002187) [15,51], including 8 samples belonging to the F. sarmentosa complex, were assembled to further explore the Ficus phylogenomics and the potential of chloroplast genomes to resolve the evolutionary relationships among the closely related species. Seven samples from the Olmedieae tribe were chosen as the outgroup, according to previous studies [26,52].…”
Section: Phylogenetic Analysismentioning
confidence: 99%